2009
DOI: 10.1007/bf03178344
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of stored wheat mycoflora, reporting theFusarium cf.langsethiae in three provinces of Iran during 2007

Abstract: -were the predominant Aspergillus species identified as exogenous mycoflora. Aspergillus flavus (26.6%) was the predominant Aspergillus species identified as endogenous mycoflora. Flotation method with MGA 0.25 recommended for isolating of hyaline fungi from wheat cereals. In this study one isolate from Fusarium species was isolated on the basis of morphology and ribosomal internal transcribed spacer classified as Fusarium langsethiae but on the basis of partial translation elongation factor-1alpha gene groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
(43 reference statements)
3
13
0
1
Order By: Relevance
“…(57.1 to 89.2%) and Alternaria spp. (82.4 to 100%) species were the predominant fungal species as endogenous mycoflora (Kachuei et al, 2009). While mycological survey carried out by Embabyet al (2012) on freshly harvested wheat grains from the main production regions in Egypt resulted in eight fungal genera isolates and some identified as: Alternaria (36.9%) and Penicillium (18.3%) were in agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…(57.1 to 89.2%) and Alternaria spp. (82.4 to 100%) species were the predominant fungal species as endogenous mycoflora (Kachuei et al, 2009). While mycological survey carried out by Embabyet al (2012) on freshly harvested wheat grains from the main production regions in Egypt resulted in eight fungal genera isolates and some identified as: Alternaria (36.9%) and Penicillium (18.3%) were in agreement with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Identification studies were further confirmed as follows by using the method described by Kachuei et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 600-bp of the PCR product was obtained and sequenced using 18 s rRNA gene-based analysis, performed by Faza Biotechnology Co. The result of the sequence analysis revealed that the fungal isolate was A. flavus (Kachuei et al 2009). …”
Section: Dna Extractionmentioning
confidence: 99%
“…The following procedures were done to identify the strain of oil-removal fungus: Colony formation on SGA was applied to find the type of fungus as previously reported by Kachuei et al (2009), special staining of Penicillium on the slide was done using lacto phenol blue. Finally, we could detect P. commune in our samples.…”
Section: Identification Of Microorganism Derived From Used Oilmentioning
confidence: 99%
“…The microbiological culture medium used in this study was SGA 4 % containing 5 g casein peptone, 5 g meat peptone, 40 g glucose and 15 g agar which were solved in 1 l distilled water and adjusted to pH 5.6 ± 0.2 at 25°C (Malik 1996;Kachuei et al 2009;Sherman et al 1991). …”
Section: Chemicals and Culture Mediamentioning
confidence: 99%